The Transnationalization of Economies, States, and Civil Societies New Challenges for Governance in Europe - Bruszt, Laszlo; Holzhacker, Ronald (Springer New York : Imprint: Springer, 2009)
Two decades after the fall of the Berlin Wall, we are witnessing an ever quickening dissolution of the boundaries between internal and external actors and the critical factors for understanding domestic institutional change. In the transnationalization of the economies of Western and Eastern Europe, international cross-ownership networks are playing a growing, and at times dominant role in domestic economies. These economies are governed by states that are increasingly sharing larger and larger parts of their regulative powers with non-domestic actors. These regulations are contested by civil societies that are increasingly based on networks of interlinked domestic and external NGOs. This is an emerging research agenda extending earlier research on transnationalization, which focused on the supra-national level, and it goes beyond the Europeanization literature that focused on externally induced or imposed change in domestic institutions. This book brings together in one volume the study of transnationalization in three institutional fields: civil society, state and the economy and extends the research of processes of transnationalization to evolving new democracies and emerging market economies. This book should be of interest to scholars and students in the field of political science, public policy, European studies, and international relations.